PROFIL KEKUATAN TARIK GELATIN DARI KULIT KAKI AYAM DAN KECEPATANPENUTUPAN LUKA PADA Mus musculus PASCA PEMBERIAN GELATIN - Nugrahaningsih, Nugrahaningsih; Lukiati, Betty; Setiowati, Frida Kunti (Universitas Sebelas Maret, 2014)
Gelatiniskind of protein extracted from animal collagen tissue. Chicken legs skin waste has not been used optimally, where as in the chicken legs skin contains collagent hatcan be extracted into gelatin. This study aims to: (1) measuring the tensile strength of gelatin produced fromthe washing process with different volumes of water flow, (2) determine the speed of enchance wound healing process in Mus musculus. Result were analyzedby ANOVA. The analysis showed differences in the volume of water flowingin the washing processafter the soakedin H2SO4did not give an affect to the tensile strength. Gelatin(P5) presence best tospeed upthe process of skin enchance wound to Musmusculus.Â Keywords: tensile strength of gelatin, enhances wound healing process